(S)-Proline-Derived Catalysts for the Acylative Kinetic Resolution of Alcohols: A Remote Structural Change Allows a Complete Selectivity Switch - Gleeson, Oliver; Gun’ko, Yurii K.; Connon, Stephen J. (Synlett, 2013)
A systematic preliminary study has identified a suite of catalysts, all readily prepared and derived from (S)-proline, which differ by a remote substituent only. If this substituent is capable of hydrogen-bond donation the catalyst will promote the resolution of secondary alcohols with the opposite sense of enantiodiscrimination to that observed when the substituent is capable of accepting hydrogen bonds.
Keywords: amines; acylation; alcohols; nucleophiles; kinetic resolution